Critical realism for health and social research - Solem, May-Britt; Jenssen, Dag (College teacher) (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book, which is aimed at the health care and social work/care field, looks at the relationship between different levels of research projects. As the social sciences can be based on quite different assumptions or 'philosophies' about what the social world is like and how knowledge about it can be obtained, this book will help students navigate the need for consistency between empirical work, the research question, research design, values and philosophy of science. Based on a critical realist perspective the book seeks to elucidate and to reflect on such connections, and to argue for the requirements of coherence as well as taking a critical look at the dilemmas that arise in health and social care/work research. Comprised of thirteen chapters which cover theoretical frameworks, research questions, objectives of the study, research ethical considerations, values, and the question of validity, it shows how these must be interlinked if a project is to have a good design. It will be of interest to researchers, PhD candidates and master's students in the field of health care and social work/care"--
Keywords: Social service -- Research; Medical care -- Research; Critical realism; SOCIAL SCIENCE / Human Services